Respuestas
Respuesta dada por:
4
1.x²-2x+7x-14
x²+5x-14
2.FÓRMULA: (a+b)(a-b)=(a)²-(b)²
x²-1
x²+5x-14
2.FÓRMULA: (a+b)(a-b)=(a)²-(b)²
x²-1
Respuesta dada por:
5
Facil hacemos la distribución
![1. ( x + 7) (x - 2) 1. ( x + 7) (x - 2)](https://tex.z-dn.net/?f=1.+%28+x+%2B+7%29+%28x+-+2%29+)
![x^{2} + 2x - 7x - 14 x^{2} + 2x - 7x - 14](https://tex.z-dn.net/?f=+x%5E%7B2%7D+%2B+2x+-+7x+-+14)
![x^{2} + 5x - 14 x^{2} + 5x - 14](https://tex.z-dn.net/?f=+x%5E%7B2%7D+%2B+5x+-+14)
![2. (x+1 ) (x-1 ) 2. (x+1 ) (x-1 )](https://tex.z-dn.net/?f=2.+%28x%2B1+%29+%28x-1+%29+)
![x^{2} + 1x - 1x - 1 x^{2} + 1x - 1x - 1](https://tex.z-dn.net/?f=++x%5E%7B2%7D+%2B+1x+-+1x+-+1)
![x^{2}+ 1 x^{2}+ 1](https://tex.z-dn.net/?f=+x%5E%7B2%7D%2B+1+)
Preguntas similares
hace 10 años
hace 10 años